MATERIAL OSTENTATION OF THE MERCANTILE ELITE OF SANTIAGO DE CHILE. CONSOLIDATION AND COHESION MECHANISMS OF A PRIVILEGED GROUP. 1716-1800. - Murillo Gordon, Ara Inmaculada (Revista de Historia Social y de las Mentalidades, 2021)
Being part of the elite in the Ancien Regime implied demonstrating the possession of economic capital, in addition to their peers and the rest of society recognizing them as such, being creditors of symbolic capital, which was manifested through ostentation. In this article we will focus on the material expressions of the Santiago mercantile elite throughout the 18th century. We analyzed documents that reflected the milestones of their lives, such as dowries, last will and testament, inventories€ we observe their access to luxury consumer goods, which shows us their privileged position and its connections in global commercial circuits.